Pendidikan Islam Dalam Perprektif Ilmunya Kuntowijoyo - Eko Sumadi (Jurnal Hikmatuna, 2018)
This article discussed the idea of Islam as the science of Kuntowijoyo, as well as trying to see the contribution of the idea in the context of the renewal of Islamic education. Similarly, the idea of Islamization of Science in responding to the hegemony of "Western" thought and culture to the Islamic world, both were distinguished by the implementation of its methodology. Not only Islamized the science and its scientists, the idea of Islam as Kuntowijoyo's knowledge was also as an effort to formulate theories of knowledge based on Islamic normative values, as a conscious effort of Muslims to make a logical and objective social transformation. Through this idea he sought to encourage the intellectual movement of the people to go further, from the reactive attitude to be proactive, by placing Islam as a viewpoint in viewing various issues of life. Meanwhile, in the renewal of Islamic education, Kuntowijoyo tried to offer an Integral-Teoantropocentric Islamic education paradigm as an effort to develop the prophetic character in Islamic education. For him, Islamic education should liberate society from all forms of oppression, injustice, and domination caused by internal and external factors. Islamic education had also to lead to the value of a character capable of lifting the human dignity of all forms of dehumanization which had resulted in them losing its essence as a living human being. In addition, Islamic education should be able to grow the character of the transcendent value so that various immoral behavior could be prevented or at least minimized.